Evaluation of the physical, chemical, bacteriological and trace metals concentrations in different brands of packaged drinking water - Jagaba, A.H. (International Association of Engineers, 2021)
âHuman survival largely depends on potable water quality. This study used current analytical procedures and compared with the National Agency for Food and Drug Administration Control (NAFDAC) drinking water specification to evaluate the physio-chemical and microbiological characteristics of fifteen packaged water brands that are available locally. Atomic absorption spectroscopy was used to determine trace metals while instrumental techniques determined the physical and chemical parameters. The evaluation focused on the pH, colour, total dissolved solids, turbidity, dissolved oxygen, fluoride, chloride, iron, zinc, magnesium, calcium, potassium, and sodium. In all the samples examined, chromium, manganese, cadmium, and copper were not detected. However, total bacterial counts were discovered in samples (S1, S2, S3, B1 and B2) with values of 2, 3, 5, 3 and 1 cfu/100 ml, respectively. Packaged water containing these type and quantity of bacteria are not fit for consumption by human beings. It requires the most appropriate techniques for processing. Â© 2021, International Association of Engineers. All rights reserved.